Enhanced Rate Capabilities of Nanobrookite with Electronically Conducting MWCNT Networks - Lee, Du-Hee; Kim, Dong-Wan; Park, Jae-Gwan (AMER CHEMICAL SOC, 2008)
Nanostructuring of intercalating electrode materials is a promising strategy in advanced lithium ion batteries with advantages of fast rate capabilities, high energy density, and excellent cycle life. However, the interparticle contact resistance caused by the easy aggregation of nanomaterials limits the electronic conduction paths and thereby reduces the power density. Herein, nanocomposites were formed by synthesizing brookite-type, TiO2 nanoparticles attached to carbon nanotubes with surfaces that had been functionalized with a cationic surfactant, cetyltrimethylammonium bromide (CTAB). The specific capacity of the nanobrookite composite incorporating carbon nanotubes was estimated to be approximately 3-fold greater than that of pure nanobrookite mechanically mixed with conventional carbon black. Furthermore, this composite electrode offers an outstanding rate capability with good capacity retention via the combined benefits of the decrease in interparticle contact resistance and one-dimensional (ID) electron transport of carbon nanotubes.
Keywords: RECHARGEABLE LITHIUM BATTERIES; LI-ION BATTERIES; CARBON NANOTUBES; NANOCOMPOSITE ELECTRODES; NANOCRYSTALLINE BROOKITE; TITANIA POLYMORPHS; TIO2-B NANOWIRES; RUTILE; INTERCALATION; ANATASE